Understanding Inherited Bleeding Disorders: Genetic Mutations in Blood Coagulation Factors and Regulatory Proteins - Ansam, Zakaria Baniamer; Aya, Mohannad Hamdan; Mohammad, Raed AlGhzawi; Mohammad, Tareq Alfaqeh; Sadeen, Yaser Yaseen; Shama, Mohammad Alshtawi; Hala, Yasin Alomush; Rand, Mahdi Olimat (Journal of Hematology and Oncology Research, 2024)
Hereditary thrombotic diseases, or inherited bleeding disorders, are a group of genetic conditions that disrupt normal blood coagulation. These diseases result from mutations in genes encoding blood coagulation factors or other regulatory proteins, impairing the body's ability to regulate bleeding and clotting. The most common inherited clotting disorders are hemophilia A and B, which are associated with deficiencies in clotting factors VIII and IX, respectively. Von Willebrand disease (VWD) is another prevalent disorder characterized by a deficiency or dysfunction of the Von Willebrand factor, a protein essential for coagulation. Additionally, the Factor V Leiden mutation is linked to an increased risk of blood clots. The prevalence of inherited coagulation disorders varies significantly by region and subpopulation. It is estimated that 5,000 to 10,000 male newborns are born with hemophilia A or B each year. Von Willebrand disease is much more common, affecting about 1% of the global population. The Factor V Leiden mutation is found in significant percentages of certain populations, with 3–8% of Caucasians being carriers. While antithrombin deficiency is more common in some areas, the incidence of other inherited clotting disorders, such as Factor XI, protein C and S deficiencies, and VWD, varies widely worldwide. This study discusses the incidence of inherited clotting disorders and their impact on affected individuals and their families. It also covers new advancements in disease management, alternative therapy approaches, and contemporary diagnostic techniques, aiming to improve diagnoses, treatments, and outcomes for patients with hereditary clotting disorders.
Keywords: Inherited Bleeding Disorders; Blood Coagulation; Genetic changes; Hereditary bleeding illnesses